New species and records of Chasmogenus Sharp, 1882 from the southwestern margin of the Guiana Shield (Coleoptera: Hydrophilidae: Acidocerinae) - Glynn, Rachel D.; Short, Andrew Edward Z. (Zootaxa, 2021)
The Neotropical water scavenger beetle genus Chasmogenus Sharp, 1882 is a diverse lineage with 34 described species. Here, three new species from the southwestern margin of the Guiana Shield are described using an integrative approach combining adult morphology and molecular data: Chasmogenus clinatus sp. n. (Brazil: Amazonas, Venezuela: Amazonas), C. gironae sp. n. (Venezuela: Amazonas), and C. inpa sp. n. (Brazil: Amazonas). Examination of the male genitalia is essential for confident identifications and thus unassociated females may prove extremely difficult to identify. New distributional records in Brazil for C. acuminatus Smith & Short, 2020 are provided as well as habitus images of newly described species and an updated key to the species from Venezuela, Suriname, Guyana, French Guiana and northern Brazil.